Would Virchow be a systems biologist?: a discourse on the philosophy of science with implications for pathological research - Stenzinger, Albrecht; Klauschen, Frederick; Wittschieber, Daniel; Weichert, Wilko; Denkert, Carsten; Dietel, Manfred; Roller, Claudio (Virchows Archiv, 2010)
Research in pathology spans from merely descriptive work to functional studies, "-omics" approaches and, more recently, systems biology. The work presented here aims at placing pathological research into an epistemological context. Aided by Rudolf Virchow, we give an overview on the philosophy of science including the Wiener Kreis, Popper, Kuhn, Fleck and Rheinberger and demonstrate their implications for routine diagnostics and science in pathology. A focus is on the fields of "-omics" and systems pathology.